Effect of Project-Based Learning on the Learning Independence of Undergraduate Students in the Family Welfare Education Program - Nurhijrah; Israwati Hamsar (Information Technology Education Journal, 2025)
This study examines the effect of Project-Based Learning (PjBL) on the learning independence of undergraduate students in the Family Welfare Education program, particularly in the Educational Evaluation course. A quasi-experimental design with a pretest–posttest non-equivalent control group was employed, involving 80 students divided into experimental (PjBL) and control (conventional) classes. Findings indicate that students taught through PjBL demonstrated stronger gains in learning independence, especially in initiative, self-management, and intrinsic motivation. These results confirm the potential of PjBL to foster autonomy in non-technical higher education contexts. The novelty of this research lies in its application of PjBL within Family Welfare Education, a field where empirical evidence remains limited. The study contributes to the development of innovative pedagogical strategies aligned with the Merdeka Belajar–Kampus Merdeka policy and offers practical insights for lecturers to enhance student self-directed learning.